Crosstalk of ferroptosis regulators and tumor immunity in pancreatic adenocarcinoma: novel perspective to mRNA vaccines and personalized immunotherapy - Shi, Yanlong; Wang, Yizhu; Dong, Hui; Niu, Kaiyi; Zhang, Wenning; Feng, Kun; Yang, Rui; Zhang, Yewei (Apoptosis (London), 2023)
Pancreatic adenocarcinoma (PAAD) is the eighth leading cause of cancer-related mortality that causes serious physical and mental burden to human. Reactive oxygen species accumulation and iron overload might enable ferroptosis-mediated cancer therapies. This study was to elusive novel ferroptosis regulator and its association with immune microenvironment and PD-L1 in PAAD. RNA-seq data and relevant information were obtained from The Cancer Genome Atlas and Genotype-Tissue Expression. The R packages “ggplot2” and “pheatmap” were used to the expression of 20 ferroptosis regulators between PAAD and normal tissues. The R package “ConsensusClusterPlus”, “survival”, “survminer”, “immunedeconv”, and TIDE algorithm performed consensus clustering, overall survival, progression-free survival, disease free survival, immune infiltration level, and immunotherapy responses between cluster 1 and cluster 2. The prognostic value was confirmed by the Kaplan–Meier curves, receiver operating characteristic curve, univariate and multivariate cox regression, and nomogram. Moreover, the relationship of FANCD2 and immunity, drug sensitivity was investigated by R package “ggstatsplot”, “immunedeconv”, “ggalluvial” and “pRRophetic”. Besides, the qRT-PCR, immunohistochemistry and western blotting detected the expression of FANCD2 in PAAD cell lines. Most ferroptosis regulators were up-regulated in PAAD, while the expression of LPCAT3, MT1G, and GLS2 was down-regulated in PAAD (P < 0.05), indicting there was a positively correlation among ferroptosis regulators. Based on clustering parameter, we identified cluster 1 and cluster 2, and cluster 2 had a better prognosis for patients with PAAD. The immune infiltration level of cluster 1 was higher in macrophage M1, myeloid dendritic cell, T cell CD4 + Th2, B cell, T cell CD8 + central memory, immune score, and microenvironment score than cluster 2 in PAAD. Moreover, FANCD2 was up-regulated in PAAD by public databases, immunohistochemistry, qRT-PCR and Western blotting, which had closely related to overall survival, immune microenvironment, and drug sensitivity. A novel crosstalk of ferroptosis exhibits a favourable prognostic performance and builds a robust theoretical foundation for mRNA vaccine and personalized immunotherapy. FANCD2 could be an effective for prognostic recognition, immune efficacy evaluation, and mRNA vaccine for patients with PAAD, providing a vital guidance for further study of regulating tumor immunity and vaccine development.